(untitled) (Revista Cocar, 2019)
Resumo O artigo propõe refletir sobre a mediação cultural e a produção artística na escola. Para isso, analisa uma das proposições do Colóquio Arte em Trânsito 2017 intitulada Crianças, artistas, mediadoras: quem aprende com quem?. O evento ocorreu no Colégio de Aplicação João XXIII na Universidade Federal de Juiz de Fora, no estado de Minas Gerais. A ação proposta foi uma visita mediada pela exposição com os licenciandos de Pedagogia da UFJF tendo as crianças-artistas como mediadoras dos trabalhos. O artigo inicia contextualizando a ação proposta, aponta questões que surgiram a partir da experiência e tece diálogos com vasta produção teórica sobre mediação cultural na busca de uma análise crítica que possibilita ampliar conexões e reflexões sobre os territórios da mediação cultural e das experiências artísticas promovidas pela escola. Palav Transit and art mediations in school: who tells the unlosable? Abstract The article proposes to reflect on cultural mediation and artistic production in school. For that, it analyzes one of the propositions of the Colloquy Art in Transit 2017 entitled Children, artists, mediators: who learns with whom?. The event took place at the João XXIII School, based at at the Federal University of Juiz de Fora (UFJF), in the state of Minas Gerais, Brazil. The proposed action was a mediated visit to the exhibition with the undergraduate students of Pedagogy from the UFJF, having the children-artists as mediators of the works. The article begins by contextualizing the proposed action, pointing out issues that have arisen from this experience and weaves dialogues with a vast theoretical production about cultural mediation in the search for a critical analysis that allows to expand connections and reflections on the territories of cultural mediation and the artistic experiences promoted by the school. Keywords: Cultural mediation; art in school; Pedagogy. ras-chave: Mediação cultural; arte na escola; Pedagogia.